Five-Year Follow-Up of a Child with Non-Syndromic Oligodontia from before the Primary Dentition Stage: A Case Report - Tatsuya Akitomo; Satoru Kusaka; Yuko Iwamoto; Momoko Usuda; Mariko Kametani; Yuria Asao; Masashi Nakano; Meiko Tachikake; Chieko Mitsuhata; Ryota Nomura (MDPI AG, 2023)
Background: Congenital absence of teeth is a major dental abnormality in pediatric dentistry and the absence of six or more teeth is defined as oligodontia. Few reports of patients with non-syndromic oligodontia without systemic disease have continued dental follow-up from an early age. Methods: We performed the five-year follow-up from before the eruption of the primary dentition of a Japanese child with non-syndromic oligodontia and analyzed changes in dental arch growth. Results: At the oral examination at the age of 1 year and 2 months, eight primary incisors were congenitally absent. Therefore, we made dentures for the patient at the age of 3 years and 4 months. From the age of 5 years and 1 month, the child received articulation training for dysarthria from a speech therapist to improve the function and appearance of the oral cavity. Measurement of the patient's dental models revealed a particularly narrow dental arch, especially between the primary canines. Conclusions: Our findings highlight the importance of treatment for patients with non-syndromic oligodontia from an early age by multiple medical professionals, recognizing that the missing teeth affect the growth of the maxillofacial region.